Concentration of hepatitis A virus in milk using protamine-coated iron oxide (Fe3O4) magnetic nanoparticles. (December 2019) - Wu, Ruiqin; Xing, Xiaohui; Corredig, Milena; Meng, Baozhong; Griffiths, Mansel W.
Abstract: Hepatitis A virus (HAV) continues to be the leading cause of viral hepatitis. HAV outbreaks have been linked to the consumption of milk, but methods for HAV detection in milk are very limited. We developed a method to concentrate HAV in milk using protamine-coated iron oxide (Fe3 O4 ) magnetic nanoparticles (PMNPs). In this study, protamine was covalently coated on the surface of the MNPs (20–30 nm) by a three-step chemical reaction. The successful linkage of protamine to the MNPs was confirmed by Fourier transform infrared spectroscopy (FTIR), zeta potential, and transmission electron microscopy (TEM). When used for concentrating HAV from 40 mL of milk, 50 μL of PMNPs were added to the sample and mixed for 20 min by gentle rotation, followed by a magnet capture for 30 min. The captured PMNPs were washed with glycine buffer (0.05 M glycine, 0.14 M NaCl, 0.2% (v/v) Tween 20, pH 9.0) and HAV RNA was extracted using the QIAamp MinElute Virus Spin Kit and quantified by real-time RT-PCR. The method showed a detection limit of 8.3 × 10 0 PFU of HAV in milk. The whole concentration procedure could be completed in approximately 50 min. The developed method was simple, inexpensive, and easy-to-perform. Highlights: Protamine-coated iron oxide (Fe3 O4 ) magnetic nanoparticles (PMNPs) were successfully fabricated. PMNPs were used to concentrate hepatitis A virus (HAV) from milk coupled with detection using real-time RT-PCR. No milk components needed to be removed for using PMNPs to capture HAV. A detection limit of 8.3 × 10 0 PFU/40 mL of HAV in milk was achieved. The PMNP capture method is simple, easy-to-perform, cost-effective, and can be completed within 50 min.